2022
DOI: 10.1002/smll.202106215
|View full text |Cite
|
Sign up to set email alerts
|

Near‐Infrared Thermally Activated Delayed Fluorescence Nanoparticle: A Metal‐Free Photosensitizer for Two‐Photon‐Activated Photodynamic Therapy at the Cell and Small Animal Levels

Abstract: Thermally activated delayed fluorescence (TADF) materials with extremely small singlet‐triplet energy offsets have opened new horizons for the development of metal‐free photosensitizers for photodynamic therapy (PDT) in recent years. However, the exploration of near‐infrared (NIR) TADF emitters for efficient two‐photon‐excited (TPE) PDT is still a formidable challenge, thus it has not been reported yet. In this study, purely organic photosensitizers (PSs) based on the TADF nanoparticles (NIR‐TADF NPs) are desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 80 publications
(51 citation statements)
references
References 68 publications
0
48
0
Order By: Relevance
“…The development of self-exciting “auto-PDT” nanoplatforms for example, where activation is driven by chemiluminescence from compounds co-loaded with the photosensitizer, extends the range of PDT and can begin to overcome barriers associated with low light penetrance into tissues [ 54 ]. The application of Near-Infrared thermally activated delayed fluorescence materials with increased efficiency of singlet oxygen generation also extends the range of PDT and is showing promise in preclinical cancer models [ 55 ]. Capitalising on the neutrophil influx in response to PDT to target delivery of nano-particles to the tumour illustrates how nanoplatforms can be rationally and effectively combined with knowledge of the biological response to PDT in order to increase its efficiency [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…The development of self-exciting “auto-PDT” nanoplatforms for example, where activation is driven by chemiluminescence from compounds co-loaded with the photosensitizer, extends the range of PDT and can begin to overcome barriers associated with low light penetrance into tissues [ 54 ]. The application of Near-Infrared thermally activated delayed fluorescence materials with increased efficiency of singlet oxygen generation also extends the range of PDT and is showing promise in preclinical cancer models [ 55 ]. Capitalising on the neutrophil influx in response to PDT to target delivery of nano-particles to the tumour illustrates how nanoplatforms can be rationally and effectively combined with knowledge of the biological response to PDT in order to increase its efficiency [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the above-mentioned potential therapeutic mechanisms related to native EVs as regenerative entities, EVs can also affect oxidative stress. Overproduction of reactive oxygen species (ROS) and resultant oxidative stress are closely associated with the pathogenesis of various diseases by breaking the redox homeostasis 88 - 94 , which will be an effective target to restore the repair and regeneration capacities. Indeed, a rich variety of research has demonstrated the ROS-scavenging and antioxidative capabilities of EVs 95 , 96 .…”
Section: Therapeutic Mechanisms Of the Native Evs As Regenerative Ent...mentioning
confidence: 99%
“…Now, MHPs have developed into a broad range of materials with the general formula ABX 3 , where A and B are monovalent and divalent cations, respectively and X stands for anions. Besides, MHPs have been widely used as active materials in various optical and electronic applications, such as photovoltaic devices (PV) ( Kojima et al, 2009 ; Kim et al, 2012 ; Lee et al, 2012 ; Jeong et al, 2021 ), light-emitting diode ( Cho et al, 2015 ; Cao et al, 2018 ; Lin et al, 2018 ), photodetector ( Li et al, 2020a ; Li et al, 2020b ), laser ( Sutherland and Sargent, 2016 ; Wei et al, 2019 ), sensor ( Zaza et al, 2019 ; George et al, 2020 ), biomedicine ( Fang et al, 2021 ; Zhang et al, 2021 ; Fang et al, 2022 ) etc.…”
Section: Emergence Of Perovskite Solar Cellsmentioning
confidence: 99%